Hepatitis C virus eradication improves immediate and delayed episodic memory in patients treated with interferon and ribavirin. Issue 1 (December 2017) - Barbosa, Mary; Zaninotto, Ana; de Campos Mazo, Daniel; Pessoa, Mario; de Oliveira, Cláudia; Carrilho, Flair; Farias, Alberto
Abstract Background Chronic hepatitis C virus (HCV) infection is associated with impairment of cognitive function and mood disorders. Our aim was to evaluate the impact of sustained virological response (SVR) on cognitive function and mood disorders. Method A prospective exploratory one arm study was conducted. Adult clinically compensated HVC patients were consecutively recruited before treatment with interferon and ribavirin for 24 to 48 weeks, according to HCV genotype. Clinical, neurocognitive and mood assessments using the PRIME-MD and BDI instruments were performed at baseline, right after half of the expected treatment has been reached and 6 months after the end of antiviral treatment. Exclusion criteria were the use of illicit psychotropic substances, mental confusion, hepatic encephalopathy, hepatocellular carcinoma, severe anemia, untreated hypothyroidism, Addison syndrome and major depression before treatment. Results Thirty six patients were enrolled and 21 completed HCV treatment (n  = 16 with SVR andn  = 5 without). Regardless of the viral clearance at the end of treatment, there was a significant improvement in the immediate verbal episodic memory (p  = 0.010), delayed verbal episodic memory (p  = 0.007), selective attention (p  < 0.001) and phonemic fluency (p  = 0.043). Patients with SVR displayed significant improvement in immediate (p  = 0.045) and delayed verbal episodic memory (p  = 0.040) compared to baseline. The baseline frequency of depression was 9.5%, which rose to 52.4% during treatment, and returned to 9.5% 6 months after the end of treatment, without significant difference between patients with and without SVR. Depressive symptoms were observed in 19.1% before treatment, 62% during (p  = 0.016) and 28.6% 6 months after the end of treatment (p  = 0.719). Conclusions Eradication of HCV infection improved cognitive performance but did not affect the frequency of depressive symptoms at least in the short range.